Sensitive and rapid detection of Culex pipiens and Aedes albopictus - Wei, Xiao; Meng, Biao; Li, Yan; Peng, Hong; Zhao, Xiangna (Frontiers in Insect Science, 2023)
Background: Culex pipiens and Aedes albopictus are closely related to human life, and transmit a variety of viruses, causing serious harm to human health. Cytochrome oxidase submit (COI) gene has been selected as a marker gene for studying phylogeny and molecular evolution of species and is also an effective molecular marker for studying the evolutionary mechanism and systematic reconstruction of diptera insects. Methods: A loop-mediated isothermal amplification (LAMP) method for the rapid and sensitive detection of Cx. pipiens and Ae. albopictus were first described in this study. The experimental results were verified by real-time PCR. Results: Our study showed the lower limit of sample concentration that can be detected by LAMP method is 0.5 pg/ul within 20 min for Cx. pipiens, and 1 pg/ul within 20 min for Ae. albopictus, which were more sensitive than PCR method. Validation tests with field samples showed LAMP method had good specificity and sensitivity and could identify the target species quickly and accurately. Conclusion: The LAMP method developed in this study allowed the rapid and sensitive detection of Cx. pipiens and Ae. albopictus, which will be expected to be used for mass screening in batches of the field.